EXPLORING THE EARLY POLITICAL HISTORY OF THE INDO-SCYTHIAN IN GANDHARA WITH SPECIAL REFERENCE TO MAUES - Jan Muhammad; Dr. Zakirullah Jan (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2023)
This paper deals with the early political history and an analysis of the Indo-Scythian from the 1st century BCE to the 1st century CE in Gandhara with special reference to Maues. Maues started his rule conceivably in 85 BCE and remained king till 57 BCE. He was the founder of this dynasty and established a strong political system on the pattern of Indo-Greek and declared Taxila as the capital city. The main objective of this paper is the reconstruction of Maues’ political history based on material culture (inscriptions and coins) found in Gandhara, while in this connection the Patika Kharoshthi inscription shedding light on the socio-political and religious conditions during the Indo-Scythian rule in this region. His coins have been discovered in most of the major archaeological sites in Gandhara, confirming his territorial jurisdiction.